Using Adobe InDesign CS5 - LoCascio, Ted (Que, 2010)
Using Adobe InDesign CS5 is more than just a book: it's the fastest, easiest way to master the InDesign skills you're looking for! You won't just read about it: you'll see it, hear it, live it, with step-by-step video tutorials and valuable audio sidebars. It's all here, including a tour of the new features in InDesign CS5, such as working with the Gap Tool, Mini Bridge, Spanning Columns, Live Corner Effects, Track Changes, Metadata Captions, and much, much more!